ANALYSIS OF THE METAVERSE UTILIZATION FOR MARKETING PURPOSE (Case Study of XYZ Pharmacy in the Netherlands) - Adintama, Digna Rayhan; Cahyaningratri, Cahyaningratri (Diponegoro Journal of Management, 2023)
ABSTRACT XYZ Pharmacy was established in 2017 and provides TelePharmacy service, Over-theCounter medicine, and Prescription medicine (Include: cannabinoid-based prescription-only medication for chronic health disorders). Since December 2022, XYZ Pharmacy has been focusing on developing its metaverse presence as a means to expand its marketing reach and create awareness among customers. Using secondary and primary data, this report will be beneficial for the company in the future as it strategizes how to build the metaverse space for reaching and presenting their developments and projects to customers. The second chapter presents key definitions and concepts associated with the metaverse, marketing, marketing channels, SWOT analysis, and the 4Ps marketing matrix. These concepts can help XYZ Pharmacy better comprehend the metaverse and digital marketing channels. In Chapter 3 of the study, the use of the metaverse as a marketing channel for XYZ Pharmacy is analyzed. It discusses the findings as well as approaches by which XYZ Pharmacy can utilize the metaverse as a marketing channel. During the research, it was discovered that the company's internal issues derive from a lack of marketing strategy and resources. This is because they are still exploring the metaverse as a marketing channel. In addition, there are some external threats that XYZ Pharmacy will face that are mentioned in this research. Therefore, in the last two chapters, the researcher gives some recommendations and perspectives that could help the company solve its problems.